Bottom-up fabrication of semiconducting 2D coordination nanosheets for versatile bioimaging and photodetecting applications. Issue 15 (8th July 2021) - Khan, Arshad; Xiang, Shuo; Zhou, Zeyan; Zhu, Chenguang; Zhang, Wei; Han, Guangze; Jiang, Kang; Li, Dong; Pan, Anlian; Weng, Qunhong
Abstract : The 2D CONASH with an optical band gap of 1.66 eV was synthesized via a simple interface reaction method, which has strong yellow photoluminescence properties. The material has application prospects in photodetection and biological imaging. Abstract : 2D coordination nanosheets (CONASHs) have gained considerable attention due to their highly flexible structures, which favor tailoring band gaps and optical and optoelectrical properties of the materials. The development of this type of 2D materials may generate advanced core materials used in electronic and optoelectronic devices. In this study, for the first time, we report the synthesis of a free-standing CONASH from a two-armed ligand and Zn via simple liquid–liquid interfacial reactions. The 2D structure was achieved by a rational design through incorporating cyanostilbene functionality into the ligand, which not only assisted in the side-by-side self-assembly of 1D polymers through hydrogen bonds but also endowed excellent photophysical characteristics. The as-synthesized nanosheets exhibited semiconducting properties with an optical band gap of 1.66 eV and strong yellow photoluminescence, which were found to label the lysosomes of mouse 4T1 cells with high brightness, specificity, and photostability. Furthermore, photodetectors fabricated based on the CONASH showed excellent photodetecting properties in a wide visible light region with the detectivity up to 6.09 × 10 11 Jones and quick responses. This study should motivate the future engineering of diversifying 2D CONASHs based on nonclassical two-arm building blocks with adjustable structural and band properties for broad optical, electrical, and optoelectrical applications.